Pengaruh Tata Ruang Kantor dan Fasilitas Kerja terhadap Kepuasan Kerja Studi Kasus BAPERLITBANG Karanganyar - Syalsabila Ashrifa Azzahro; Patni Ninghardjanti; Nur Rahmi Akbarini (Politeknik Kampar, 2023)
Badan Perencanaan and Pengembangan Kabupaten Karanganyar is the focus of this study. The purpose of this research is to determine whether there is an influence of workplace facilities and office spatial arrangement on the job satisfaction of employees in the Planning, Research, and Development Agency of Karanganyar Regency. The data collection method used in this study is quantitative research. The sampling technique employed is non-probability sampling or saturated sampling with a total of 48 respondents. Data collection techniques include observation, interviews, and questionnaires. The research instruments were tested for validity and reliability. Data analysis in this study was conducted using descriptive data analysis, classical assumption tests, multiple linear regression analysis, hypothesis testing, and dominant effect testing using SPSS 25.0 Version. The results of this study indicate that 1) workplace facilities have a significant influence on job satisfaction, 2) office spatial arrangement has a significant influence on job satisfaction, and 3) workplace facilities and office spatial arrangement jointly affect job satisfaction.